Understanding the Paratransit and Intermediate Public Transport (IPT) Services in Rangpur City of Bangladesh: The Case on E-rickshaws - Pramanik, Md Ashrafuzzaman; Rahman, M Shafiq Ur (Journal of Bangladesh Institute of Planners, 2020)
Mobility of many people in Bangladesh, particularly in the medium-sized cities, are dependent on paratransit or intermediate public transport (IPT) modes. The E-rickshaws (battery-operated electric three-wheelers), which usually provides a very flexible and demand-responsive services, as a form of paratransit/IPT is a common mode in many cities. The main purpose of this paper is to discuss the operational characteristics of E-rickshaws as a paratransit/IPT mode in Bangladesh and the trip characteristics of E-rickshaw users. A case study was done in Rangpur City. A total 397 E-rickshaw operators or drivers were interviewed to identify the factors influencing the operations and services. A total 400 passengers of E-rickshaws were interviewed for collecting information about their trip characteristics. Four types of paratransit modes are operating in Rangpur city are: cycle-rickshaws, battery-rickshaws, E-rickshaws (also called as ‘auto’) and CNG. Survey data reveal that around 74% of the passengers choose E-rickshaw for their trips. Existing E-rickshaw users are satisfied with the services compared to other travel modes. The performance index calculation for the fare rate of E-rickshaws was found to be 4.4, where 0 is for the worst and 5 is for the excellent. Now, as the majority of city dwellers are using E-rickshaws for their travel, complete banning or restricting of E-rickshaws will have devastating effects on urban transport system and passengers travel as well as drastic negative impacts on the earnings or livelihood of drivers/operators. The results of this paper would be helpful for the government, particularly for city authority, and the relevant agencies to formulate policy guidelines for E-rickshaws as well as other paratransit or IPTs. JBIP, Vol. 13, 2020 (Printed in June 2021), pp. 89-110